129k views
5 votes
(p+3t/6) ÷ (p÷6) p=6 t=4

2 Answers

2 votes
Use PEMDAS.

6 + 3(4) / 6
6 + 12 / 6
6 + 2 = 8


6 / 6 = 1


8 / 1 = 8

I hope this helped.
User Jared Reeves
by
4.8k points
3 votes

Answer:

(p+3t/6) ÷ (p÷6) = 8

Step-by-step explanation:

(p+3t/6) ÷ (p÷6)

Given that:

p=6 AND t=4

Putting values of p and t in equation:

=(6+3(4)/6)/ (6/6) First we will solve the round brackets

=(6+12/6)/(1) As 3*4 =12

=(6+2) As 12/6 = 2 and anything dividing by one remains same

=8 Answer

User Villi Magg
by
6.7k points